1992
DOI: 10.1093/protein/5.7.693
|View full text |Cite
|
Sign up to set email alerts
|

Site-saturation mutagenesis and three-dimensional modelling of ROB-1 define a substrate binding role of Ser 130 in class A β-lactamases

Abstract: Site-saturation mutagenesis was performed on the class A ROB-1 beta-lactamase at conserved Ser130, which is centrally located in the antibiotic binding site where it can participate in both protein-protein and protein-substrate hydrogen bonding. Mutation Thr130 gave a beta-lactamase hydrolysing penicillins and cephalosporins but which showed a 3-fold lower affinity (Km) for ampicillin and cephalexin, and a 30-fold lower hydrolytic (Vmax) activity for ampicillin. In contrast, the hydrolytic activity for cephale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0
3

Year Published

1994
1994
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 0 publications
5
50
0
3
Order By: Relevance
“…The major effect of the S130G mutation on apparent K m and K I emphasizes the precise topological role of this amino acid (17,(22)(23)(24)(25)(26)(27). A direct consequence of the Ser 3 Gly substitution is reflected by the amount of S130G versus SHV-1 inhibited in 20 min, the time required for E. coli cell division.…”
Section: Discussionmentioning
confidence: 99%
“…The major effect of the S130G mutation on apparent K m and K I emphasizes the precise topological role of this amino acid (17,(22)(23)(24)(25)(26)(27). A direct consequence of the Ser 3 Gly substitution is reflected by the amount of S130G versus SHV-1 inhibited in 20 min, the time required for E. coli cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Mutational studies have demonstrated that substitutions at residues Ser-130 and Ser-235 result in a significant decrease in cephalosporinase activity, and yet do not greatly alter penicillinase activity (25,26). Each study proposed that the loss of a hydrogen bond to the substrate carboxylate from the serine side chain was detrimental only for cephalosporin hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion from these studies was that the hydrogen bond network in the active site is developed to such an extent for penicillinase activity that the enzyme can afford the mutational loss of one or two hydrogen bonds and retain function. For example, it was proposed that the S130G mutation was compensated for in penicillin hydrolysis by a hydrogen bond to the substrate carboxylate from Arg-244 that is shorter (stronger) for penicillins than for cephalosporins (26). Therefore, because the TEM enzyme has more interactions with penicillins than with cephalosporins, the loss of any specific interaction due to a residue substitution is critical to cephalosporin hydrolysis and therefore is not tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Ser130 mutants have less substrate affinity. 39,40) Several structural studies on the acylenzyme intermediate analogues indicated that Ser130 made a hydrogen bond with the carboxyl group. 7,[41][42][43] From these experimental findings, the function of Ser130 was thought to be binding a substrate.…”
Section: Deacylation Mechanism Of Class a B-lacta-masementioning
confidence: 99%